THE APPLICATION OF ARTIFICIAL INTELLIGENCE TOOLS IN JOURNALISM IN KAZAKHSTAN (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article provides an in-depth, chronologically grounded analysis of the integration of artificial intelligence (AI) technologies into journalism in the Republic of Kazakhstan. Starting with President Kassym-Jomart Tokayev’s speech at the National Congress, the study explores the development of the country’s digital media infrastructure, the establishment of innovative research centers such as “AI MediaLab” and “LG AI MediaLab,” and the creation of the first AI-powered convergent newspaper, “AI-Tamyz.” It also covers the publication of fundamental popular-scientific works like The Alphabet of Artificial Intelligence. The article discusses international experiences and addresses key issues related to ethics, mental well-being, social responsibility in journalism, inclusivity, and information equality in the context of AI. The findings indicate that Kazakhstan is not only advancing technologically but is also striving to integrate artificial intelligence into journalism in a way that preserves national values. This article offers relevant theoretical and practical conclusions for scholars and professionals engaged in AI integration in media, journalism education, information policy, and digital inclusion.